Analisis Bahasa Figuratif dalam Antologi Puisi Mastera Dari Amerika ke Catatan Langit Kurator Dendy Sugono - Yolanda Virnanci; Mohd. Harun; Herman R Herman R (JIM Pendididikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the figurative language contained in the Anthology of Master's Poetry from America to Heavenly Notes using a qualitative approach. This type of research is a qualitative descriptive study. Technique data were carried out using coding techniques. The data were analyzed through the empathy stages, namely, classification, classification, analysis, and description. The results of this study indicate that the figurative language contained in the poetry collection from America to Notes Langit, curator Dendy Sugono, has 8 types of figurative languages, namely metaphor, simile, personification, hyperbole, irony, metonymy, sarcasm and rhetoric. There are three types of figurative language that are the most dominant, 10 poems of simile figurative language, 9 poems of personified figurative language, and 8 poems of metaphorical figurative language, while the least figurative language is metonymy and sarcasm, 1 poetry each. The use of figurative language in the Anthology of Mastera Poetry from America to Heaven's Notes Curator Dendy Sugono serves as an explanation of every meaning and bait of poetry created by the poet.